A Root Cause Analysis of Barriers to Timely Colonoscopy in California Safety-Net Health Systems. Issue 1 (28th May 2020) - Sharma, Anjana E.; Lyson, Helena C.; Cherian, Roy; Somsouk, Ma; Schillinger, Dean; Sarkar, Urmimala
Abstract : Objectives: Safety-net health care systems, serving vulnerable populations, see longer delays to timely colonoscopy after a positive fecal occult blood test (FOBT), which may contribute to existing disparities. We sought to identify root causes of colonoscopy delay after positive FOBT result in the primary care safety net. Methods: We conducted a multisite root cause analysis of cases of delayed colonoscopy, identifying cases where there was a delay of greater than 6 months in completing or scheduling a follow-up colonoscopy after a positive FOBT. We identified cases across 5 California health systems serving low-income, vulnerable populations. We developed a semistructured interview guide based on precedent work. We conducted telephone individual interviews with primary care providers (PCPs) and patients. We then performed qualitative content analysis of the interviews, using an integrated inductive-deductive analytic approach, to identify themes related to recurrent root causes of colonoscopy delay. Results: We identified 12 unique cases, comprising 5 patient and 11 PCP interviews. Eight patients completed colonoscopy; median time to colonoscopy was 11.0 months (interquartile range, 6.3 months). Three patients had advanced adenomatous findings. Primary care providers highlighted system-level root causes, including inability to track referrals between primary care and gastroenterology, lack of protocols to follow up with patients, lack of electronic medical record interoperability, and lack of time or staffing resources, compelling tremendous additional effort by staff. In contrast, patients' highlighted individual-level root causes included comorbidities, social needs, and misunderstanding the importance of the FOBT. There was a little overlap between PCP and patient-elicited root causes. Conclusions: Current protocols do not accommodate communication between primary care and gastroenterology. Interventions to address specific barriers identified include improved interoperability between PCP and gastroenterology scheduling systems, protocols to follow-up on incomplete colonoscopies, accommodation for support and transport needs, and patient-friendly education. Interviewing both patients and PCPs leads to richer analysis of the root causes leading to delayed diagnosis of colorectal cancer.